Validation of Total Daily Energy Expenditure Calculated with Actiheart against Doubly Labeled Water Method in Costa Rican Schoolchildren - Zamora Salas, Juan Diego (2015)
The purpose of this study was to use the measurement of the PAEE taken from Actiheart in order to calculate the TEE in Costa Rican schoolchildren, and at the same time, to determine the effec- tiveness when it is compared against the TEE obtained by the DLW. A total of sixteen male schoo l- children were measured for their total daily energy expenditure (TEE) with the doubly labeled water (DLW) technique. The TEE obtained by the Actiheart monitor was calculated and validated against the DWL. The TEE was obtained adding the physical activity energy expenditure given by the Actiheart, plus the basal metabolic rate, and the energy cost of growth. The Pearson’s product - moment correlation coeffi cient a nd the paired t -test sample were measured in order to identify the association of the data and to evidence the differences between both measurements of TEE respectively. The Lin’s concordance correlation coefficient and the Bland -Altman plot evaluated the concordance of both methods. The correlation between the TEE obtained by DLW and the one calculated by Actiheart was r = 0.97, P < 0.001. The paired t -test showed no significant differences between both methods. Lin’s concordance correlation coefficient wa s Cb = 0.99, classified as a l- most perfect. The study validated the TEE calculated with Actiheart against the TEE measured by the DLW.